Moringa Oleifera Lam. in Cardiometabolic Disorders: A Systematic Review of Recent Studies and Possible Mechanism of Actions - Louisa, Melva; Patintingan, Cyntia Gracesella Hutami; Wardhani, Bantari W. K. (Frontiers in Pharmacology, 2022)
Cardiometabolic disorders (CMD) have become a global emergency and increasing burden on health and economic problems. Due to the increasing need for new drugs for cardiometabolic diseases, many alternative medicines from plants have been considered and studied. Moringa oleifera Lam. (MO), one of the native plants from several Asian countries, has been used empirically by people for various kinds of illnesses. In the present systematic review, we aimed to investigate the recent studies of MO in CMD and its possible mechanism of action. We systematically searched from 3 databases and summarized the data. This review includes a total of 108 papers in nonclinical studies and clinical trials of MO in cardiometabolic-related disorders. Moringa oleifera, extracts or isolated compound, exerts its effect on CMD through its antioxidative, anti-inflammatory actions resulting in the modulation in glucose and lipid metabolism and the preservation of target organ damage. Several studies supported the beneficial effect of MO in regulating the gut microbiome, which generates the diversity of gut microbiota and reduces the number of harmful bacteria in the caecum. Molecular actions that have been studied include the suppression of NF-kB translocation, upregulation of the Nrf2/Keap1 pathway, stimulation of total antioxidant capacity by reducing PKCζ activation, and inhibiting the Nox4 protein expression and several other proposed mechanisms. The present review found substantial evidence supporting the potential benefits of Moringa oleifera in cardiovascular or metabolic disorders